Is Islamic Finance ethical finance? Principles and Stakeholder Responsibilities - Hamzah, Shariza (2011)
With the recent global financial crisis and the many scandals that have happened of late, there is a need for an ethical finance system. Reports have mentioned and concluded that Islamic financial institutions were the least to be affected, with more than US$800 billion worth of deposits and investments lodged, Islamic banks, mutual funds, insurance schemes, and Islamic branches of conventional banks (Hesse et al, 2008). Would it be fair then to say that Islamic finance is ethical finance? There are many initiatives done by various entities; for instance the Equator Principles (EP) by the International Finance Corporation (IFC), and Principles of Responsible Investment (PRI) by the United Nation Environment Programme Finance Initiative (UNEP FI), both taking the environment, social and governance (ESG) issues into consideration. This project attempts to analyse whether Islamic Finance satisfy all themes in the need of ethics in finance; market, industry, management and people (Boatright, 1999) by making comparative analysis between EP, PRI and Shari'ah Principles (the basis of Islamic Finance). Taking a step further, the analysis looks upon the Islamic financial institutions in Malaysia, and their stakeholder responsibilities in marketplace, workplace, environment and community.